Barriers to Smoking Cessation among Medical Students 2012â2013 Academic Year in the Faculty of Medicine, Universitas Padjadjaran - Kathrine, Reni Yuditha; Setiawati, Elsa Pudji; Saputra, Lucky (Althea Medical Journal, 2015)
Background: Smoking is one of leading various diseases and even death globally.Â It is often difficult for smokers to stop smoking, even those who work as a medical professional because there are some barriers around them. The objective of this study was to get an overview of the barriers to smoking cessation among smoker students of Faculty of Medicine, Universitas Padjadjaran.Methods: A descriptive study was carried out to 62 medical students 2012â2013 academic year in the Faculty of Medicine, Universitas Padjadjaran. Before the respondents were selected, a survey using questionnaire was conducted to all medical students from the same academic year to determine their smoking status. A set of questions was developed, consisted of 4 components: physical or social, psychological or emotional, accessibility, and social contextual/life circumstances barriers to smoking cessation. The collected data were analyzed and presented in the form of percentages shown in the tables and figures.Results: The most frequent barriers were from physical or social barriers (friends who smoke, 85%), psychological or emotional barriers (fear of losing enjoyment, 71%), barrier to access (lack of information about the way of smoking cessation, 42%) and social contextual/life circumstances barriers (having other priorities other than to stop smoking, 71%).Conclusions: There are some barriers in medical students smokers make them difficult to stop smoking although they have more knowledge about health and the impact of smoking on health than other people.Â DOI:Â 10.15850/amj.v2n3.561